2021
DOI: 10.3389/fimmu.2021.637809
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Th1 T Cell Differentiation by Iron via Upregulation of T Cell Immunoglobulin and Mucin Containing Protein-3 (TIM-3)

Abstract: Iron plays an important role in host–pathogen interactions, in being an essential element for both pathogen and host metabolism, but also by impacting immune cell differentiation and anti-microbial effector pathways. Iron has been implicated to affect the differentiation of T lymphocytes during inflammation, however, so far the underlying mechanism remained elusive. In order to study the role of iron in T cell differentiation we here investigated how dietary iron supplementation affects T cell function and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Similarly, injection of wild-type mice on a standard diet with iron dextran, which increases serum iron, does not induce CD8+ T-cell proliferation beyond normal levels after immunisation ( 3 ). Recently, it has been reported that high iron concentrations may suppress CD4+ T-cell proliferation and Th1 differentiation ( 53 ), indicating that there may be complex context-dependent effects of excess iron on CD4+ T-cells. These data indicate that while iron supplementation may be able to boost immunity in individuals with existing iron deficiency, supplementing iron in iron replete individuals may provide little benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, injection of wild-type mice on a standard diet with iron dextran, which increases serum iron, does not induce CD8+ T-cell proliferation beyond normal levels after immunisation ( 3 ). Recently, it has been reported that high iron concentrations may suppress CD4+ T-cell proliferation and Th1 differentiation ( 53 ), indicating that there may be complex context-dependent effects of excess iron on CD4+ T-cells. These data indicate that while iron supplementation may be able to boost immunity in individuals with existing iron deficiency, supplementing iron in iron replete individuals may provide little benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The number of mature T cells will decrease if ferritin H is knocked out in the bone marrow ( 53 ), which suggests that iron stored in ferritin is necessary for lymphocyte survival. Recent studies demonstrated that iron inhibits Th1 cells differentiation and expression of interferon-gamma (IFN-γ) ( 54 ). Besides, studies showed that iron inhibits Th1 lymphocyte activity ( 55 ).…”
Section: Iron and T Cellsmentioning
confidence: 99%
“…Iron is another micronutrient that is required by the immune system for proper functioning. Iron is important to maintain thymus function and the output of naive T lymphocytes and also to support neutrophil respiratory burst and bacterial killing, NK cell activity, T lymphocyte proliferation and production of T helper 1 cytokines ( 99 101 ) ( Figure 2 ). These observations would suggest a clear case for iron deficiency increasing susceptibility to infection, which it does ( 102 ).…”
Section: Micronutrients: Support Of Normal Immune Function and Releva...mentioning
confidence: 99%